Analysis of biomarkers of inflammation and oxidative stress in chagas disease - Martí, María Belén (2016)
Introduction: The pathophysiologic factors that control the formation and perpetuation of heart inflammation in chagasic patients were not yet fully clarified. Chronic inflammatory processes induce oxidative/nitrosative stress and lipid peroxidation.